Penggunaan Media Teks Bergambar Dalam Meningkatkan Kemampuan Membaca Siswa Tunagrhita Kelas III DI SLB Negeri 1 Gowa - Muh Syarif Hidayatullah; Hadis Hadis; Triyanto Pristiwaluyo (-, 2023)
This study examines the reading ability of third grade mentally retarded students at SLB Negeri 1 Gowa using pictorial text media. The formulation of the research problem is "Can the use of pictorial text media improve the reading ability of third grade mentally retarded children in SLB Negeri 1 Gowa?". The aims of this study were 1) the reading ability of a third grade mentally retarded child in SLB Negeri 1 Gowa before the use of pictorial text media 2) the reading ability of a third grade mentally retarded child in SLB Negeri 1 Gowa with the use of pictorial text media 3) improving reading skills in a third grade mentally retarded student at SLB Negeri 1 Gowa using pictorial text media. This research approach is a quantitative approach with descriptive research type, namely to describe the improvement of reading skills before and after the use of illustrated text media in grade III mild mentally retarded students at SLB Neferi 1 Gowa. The subject of this study was a class III mentally retarded child at SLBN 1 Gowa with the initials AN. The data collection technique was a reading test. Data analysis used test results before and after treatment, describing test results before and after treatment. The conclusions of this study are 1) The reading ability of a third grade mentally retarded child at SLB Negeri 1 Gowa before the use of illustrated text media was in the poor category; 2) The ability to read in a class III mentally retarded child at SLB Negeri 1 Gowa with the use of illustrated text media is in the already capable category; 3) There is an increase in reading ability in a third grade mentally retarded student at SLB Negeri 1 Gowa by using illustrated text media from the unable category to the already able category.